Tuning RED for Web traffic. - Christiansen, Mikkel (Computer communication review.)
We study the effects of RED on the performance of Web browsing with a novel aspect of our work being the use of a user-centric measure of performance: response time for HTTP request-response pairs. We empirically evaluate RED across a range of parameter settings and offered loads. Our results show that: 1) contrary to expectations, compared to a FIFO queue, RED has a minimal effect on HTTP response times for offered loads up to 90% of link capacity; 2) response times at loads in this range are not substantially affected by RED parameters; 3) between 90% and 100% load, RED can be carefully tuned to yield performance somewhat superior to FIFO, however, response times are quite sensitive to the actual RED parameter values selected; and 4) in such heavily congested networks, RED parameters that provide the best link utilization produce power response times. We conclude that for links carrying only Web traffic, RED queue management appears to provide no clear advantage over tail-drop FIFO for end-user response times.